Medidas de autoprotección en redes sociales. Análisis de los hábitos de los usuarios de Facebook, Instagram y Twitter - Solari Merlo, Mariana Noelia (Archivos de criminología, seguridad privada y criminalística, 2021)
The widespread acceptance of social networks has made them one of the main spaces for interaction in the virtual sphere, where citizens not only relate to each other but also share personal information about various aspects of their lives. In this sense, various studies have analyzed the crime that originates in these environments in light of the Routine Activities Theory, especially observing the habitual behavior of the users themselves as potential victims of these crimes. The present work constitutes an empirical study of the habits of the users in the matter of security but, in this case, focused exclusively on those aspects that are directly related to self-protection and, specifically, the behaviors associated with passwords.